Enabling Security in Cloud Storage SLAs with CloudProof - Molnar, David; Lorch, Jay; Wang, Helen; Popa, Raluca Ada; Zhuang, Li (2010)
Several cloud sotrage systems exist today, but none of them provide security guarantees in their Service Level Agreements (SLAs). This lack of security support has been a major hurdle for the adoption of cloud services, especially for enterprises and cautious consumers. To fix this issue, we present CloudProof, a secure storage system specifically designed for the cloud. In CloudProof, customers can not only detect violations of integrity, write-serializability, and freshness, they can also prove the occurrence of these violations to a third party. This proof-based system is critical to enabling security guarantees in SLAs, wherein clients pay for a desired level of security and are assured they will receive a certain compensation in the event of cloud misbehavior. Furthermore, since CloudProof aims to scale to the size of large enterprises, we delegate as much work as possible to the cloud and use cryptographic tools to allow customers to detect and prove cloud misbehavior. Our evaluation of CloudProof indicates that its security mechanisms have a reasonable cost: they incur a latency overhead of only 15% on reads and writes, and reduce throughput by around 10%. We also achieve highly scalable access control, with management of source code for a large proprietary software with more than 5000 developers taking only a few seconds per month.